Temporal study of urban growth and land surface temperature extraction: a study of the Klang Valley area / Illyani Ibrahim ... [et al.] - Ibrahim, Illyani; Abu Samah, Azizan; Fauzi, Rosmadi (2014)
century. A physical aspect that needs to be understood is the urban climate problem such as the urban heat island phenomenon and its factors and effects towards environment. The steady economic growth and rapid urbanization has created more concrete landscapes that can increase the level of discomfort for the population especially in the Klang Valley region. The problem is worsening in the Klang Valley area which is plagued by extensive economic activities and the heat generated from factories, transport and air conditioners. As such, this study examines the expansion of urban growth and the temporal pattern of the land surface temperature which has influenced the quality of air quality. This study utilizes the Landsat images for different time periods and unsupervised classification had been carried out to retrieve the land cover types. In order to isolate effects of urbanization on surface temperature, the comparison of the historical datasets of air temperature in rural and urban areas are studied. This image was processed for appropriate atmospheric and geometric correction and the extraction of land surface temperature by using the model of the mono-window algorithm. Our findings show that the rate of urbanization of the study area is 37.725 km square per year. Next, this study also shows that the urban areas have extensively expanded more than thrice in 1999 compared to 1989. Further finding of this study is that two greenery areas have a higher average temperature. However, future study will look at the main concern of the key factors can be applied by the local urban planning authority in applied climatology and remote sensing study.